Characterization of petroleum sulfonate synthesized via gas-phase SO3 sulfonation in rotating packed bed and its application in enhanced oil recovery. (2nd February 2021) - Ma, Xiaoke; Liu, Bing; Ma, Tianxiang; Zou, Hai-Kui; Chu, Guang-Wen; Sun, Bao-Chang; Zhang, Liangliang; Luo, Yong; Chen, Jian-Feng
Highlights: PS with good EOR performance was prepared via gas-phase SO3 sulfonation in the RPB. The definite chemical composition of PS was characterized at the molecular level. The CMC method was adopted for the optimization of the PS surfactant concentration. Abstract: In this work, petroleum sulfonate (PS), which can be used for enhanced oil recovery (EOR), was synthesized by sulfonation of distillate oil using gaseous SO3 in a rotating packed bed. The prepared PS was characterized by FT-IR, NMR, negative electrospray ionization fourier transform ion cyclotron resonance mass spectrometry [(−) ESI FT-ICR MS] and thermal gravimetric analysis (TGA). Results showed that the PS contains N1, O1, O2, O3, N1O2, O3S, O4S, and N1O3S classes, among which O3S, O4S, and N1O3S are the three main classes. And the chemical composition of the PS was obtained by the combined analysis of the double-bond equivalent (DBE) and carbon number (CN). TGA results showed that PS is thermally stable at the conventional reservoir temperature (less than 200 °C). In addition, the EOR performance of PS was studied by measuring surface tension, interfacial tension (IFT), wettability alteration and core-flooding experiments. Critical micelle concentration (CMC) of the prepared PS with a value of 0.2% was also determined by surface tension method. An ultra-low oil-water IFT value 1.327 × 10 −3 mN/m was obtained at the CMC of PS solution. It was also found that adding PS into brine can decrease the contact angle below 90°, indicating that it can alter the rock wettability from oil-wet to water-wet surface which contributes to enhancing oil recovery. Finally, core-flooding experiments were carried out with different PS concentrations. The results showed that an additional recovery of about 30% after conventional water flooding can be obtained at a PS concentration of 0.3%. This study indicated that the PS synthesized by gas-phase SO3 sulfonation in RPB has good EOR performance, and the work is helpful for the learning of the relationship between PS composition and EOR performance and give the guidance for PS's synthesis.